Meanings of Bandung : postcolonial orders and decolonial visions - Phạm, Quỳnh N., 1985-; Shilliam, Robbie, 1969- (Kilombo : international relations and colonial questions, 2016)
"Provides an interdisciplinary retrieval of the multiple meanings of decolonization that the famous Bandung Conference (1955) holds for the study of international relations"--